2021
DOI: 10.1177/03635465211036141
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Timing of Anterior Cruciate Ligament Reconstruction and Chondral Injuries: A Systematic Review and Meta-analysis

Abstract: Background: After anterior cruciate ligament (ACL) injury, the optimal timing of ACL reconstruction and the influence of this timing on chondral damage remain unclear. Purpose: To assess the effect of timing of ACL reconstruction on the presence of chondral injuries via a systematic review and meta-analysis. Study Design: Systematic review and meta-analysis; Level of evidence, 4. Methods: Two reviewers independently performed systematic literature searches of 5 online databases using the Cochrane methodology f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 55 publications
(177 reference statements)
3
14
0
Order By: Relevance
“…ACL reconstruction performed >3 months after the injury was associated with higher medial meniscal tear incidence compared with procedures performed within 3 months after the injury; however, there was no difference in lateral meniscal tear incidence. Similarly, Prodromidis et al 5 found increasing rates of chondral injury associated with ACL reconstruction procedures performed at 3 months, 6 months, and 12 months after the injury. In ACL reconstruction procedures performed at 3 months, the chondral injuries were primarily low-grade, whereas, in those procedures performed at 12 months, the injuries were predominantly high-grade.…”
Section: Kneementioning
confidence: 86%
“…ACL reconstruction performed >3 months after the injury was associated with higher medial meniscal tear incidence compared with procedures performed within 3 months after the injury; however, there was no difference in lateral meniscal tear incidence. Similarly, Prodromidis et al 5 found increasing rates of chondral injury associated with ACL reconstruction procedures performed at 3 months, 6 months, and 12 months after the injury. In ACL reconstruction procedures performed at 3 months, the chondral injuries were primarily low-grade, whereas, in those procedures performed at 12 months, the injuries were predominantly high-grade.…”
Section: Kneementioning
confidence: 86%
“…26 Understanding the extent to which the decrease in surgical volume was due to decreased injury versus delayed surgery is important because studies have shown that ACLR delays are associated with worse outcomes. [10][11] It is customary to schedule ACLR within 3 months of injury due to the potential negative effects associated with delaying surgery, such as increased chondral lesions and increased risk of meniscal injuries and irreparable meniscal tears. [10][11] This became more difficult as many elective surgeries were delayed or cancelled due to the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11] It is customary to schedule ACLR within 3 months of injury due to the potential negative effects associated with delaying surgery, such as increased chondral lesions and increased risk of meniscal injuries and irreparable meniscal tears. [10][11] This became more difficult as many elective surgeries were delayed or cancelled due to the COVID-19 pandemic. [8][9] As providers counsel patients about preferred surgical timing for ACLR, both during the COVID-19 pandemic and beyond, they must consider the negative impact of delayed ACLR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Timing prior to the procedure is also an important biomechanical consideration. While waiting can calm inflammation to enhance repair potential, it must be balanced with the increased risk of other injuries that can occur in this timeframe ( Fok and Yau, 2013 ; Kolin et al, 2021 ; Prodromidis et al, 2021 ).…”
Section: Other Joint Factors That Influence Healingmentioning
confidence: 99%